KEPEMIMPINAN PEMERINTAH DAERAH DALAM PERSPEKTIF ETIKA PUBLIK - Maskan AF (Prodi Ilmu Administrasi Negara, 2020)
Leaders are the center of everything for those who are led, they have the capacity, ability, and integrity, and become an example and role model for their subordinates, so they must understand the ethical and moral values and be able to realize them in carrying out their leadership processes.To get a leader as a criterion required above requires a system and process of recruitment and regeneration according to good mechanisms so that good leaders will be found. But in reality at the moment the political party as the leader cadre printing whoever will advance in the regional head election contestation must go through the party vehicles, but not all of them have carried out the pattern of recruitment and regeneration as it should be, precisely what is done is kinship politics, and instant regeneration as a result many party cadres who became a leader in the area was not able to carry out the duties and responsibilities delegated to the leader maximally, instead it was proven that several regional heads stumbled over legal problems due to misusing their positions for personal, family and group interests.